KEPATUHAN ADMINISTRASI RUMAH SAKIT SWASTA DAN PEMERINTAH TERHADAP STANDAR PELAYANAN KESEHATAN - Hotmaria Hertawaty Sijabat (CV. Adiba Aisha Amira, 2025)
This study examines the administrative compliance of private and government hospitals with established health service standards. Compliance varies significantly, with government hospitals tending to be more compliant due to strict supervision and binding regulations, although there are still shortcomings in certain aspects. On the other hand, private hospitals demonstrate flexibility in implementing standards, but sometimes face obstacles such as business orientation, resource constraints, and management issues. Nevertheless, some private hospitals have successfully created service innovations that align with or even exceed established standards. To achieve optimal compliance in both types of hospitals, intensive supervision, continuous training, and synergy between the government, regulatory bodies, and hospitals are required. The results of this study are expected to encourage improvements in the quality of healthcare services in Indonesia.